Mendampingi Single Parent Kristen: Pastoral Konseling dengan Teknik Psikoedukasi dalam Menghadapi Kesulitan Hidup - Kamadjadja, Djumailah; Hindradjat, Juliana (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2024)
This research aims to understand how pastoral counseling with psychoeducation techniques can help Christian single parents face life's difficulties. This research uses a literature study method by analyzing relevant books, scientific journals, and online articles. The research results show that pastoral counseling with psychoeducation techniques can help Christian single parents increase knowledge and understanding about themselves and the situations they face. Read coping skills for dealing with stress and anxiety. Build positive relationships with others. They are strengthening their faith and trust in God. The conclusion of this research shows that pastoral counseling with psychoeducation techniques is an effective intervention to help Christian single parents face life's difficulties.